Pro‐vitamin A carotenoid content of 48 plantain (Musa AAB genome) cultivars sourced from eastern Democratic Republic of Congo. (25th November 2019) - Blomme, Guy; Ocimati, Walter; Nabuuma, Deborah; Sivirihauma, Charles; Davey, Mark; Buah, Stephen; Van den Bergh, Inge; Vutseme, Lusenge; Bahati, Liliane; Ekesa, Beatrice
Abstract: BACKGROUND: Vitamin A deficiency (VAD) is widespread in sub‐Saharan Africa (SSA). Unlike in developed countries, where the main source of vitamin A comes from meat, the diet of poor populations in SSA is largely plant based. It is thus important to identify local / popular plants with higher vitamin A content for combating VAD. Banana (including plantains) is an important staple food crop in this region. The identification and promotion of vitamin A‐rich banana cultivars could contribute significantly to the alleviation of VAD in areas heavily dependent on the crop. We assessed pro‐vitamin A carotenoid (pVACs) content in the fruit pulp of 48 local plantains from eastern Democratic Republic of Congo, to identify cultivars that could help reduce VAD, especially among young children and women of reproductive age. RESULTS: Mean pVACs content varied from 175–1756 μg/100 gfw in ripe fruits. Significant increases ( P  < 0.001) in total pVACs content occurred after ripening in all cultivars except 'UCG II'. Retinol activity equivalents (RAE) in ripe fruits ranged from 12–113 μg/100 gfw. Fifteen plantain cultivars, including 'Adili II', 'Nzirabahima', 'Mayayi', 'Buembe', and 'Sanza Tatu' (associated with RAE values of 44 μg/100 gfw and above) can be considered as good sources of pVACs. Modest consumption (250 or 500 gfw) of the fruit pulp of the five best plantain cultivars at ripening stage 5 meets between 39–71% and 44–81% of vitamin A dietary reference intake (DRI) respectively, for children below 5 years old and women of reproductive age. CONCLUSION: The 15 best plantain cultivars (especially the top 5) could potentially be introduced / promoted as alternative sources of pro‐vitamin A in banana‐dependent communities, and help to reduce cases of VAD substantially. © 2019 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.